2020
DOI: 10.1016/j.ajogmf.2020.100114
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of the bactericidal effects of chlorhexidine vs povidone-iodine vaginal preparation

Abstract: BACKGROUND: Precesarean vaginal preparation significantly reduces postpartum infections. Although povidone-iodine is the most commonly used vaginal antiseptic, evidence suggests that chlorhexidine gluconate may be more effective. OBJECTIVE: We aimed to compare the bactericidal effect of chlorhexidine gluconate and povidone-iodine on vaginal bacterial colony counts in pregnancy. MATERIALS AND METHODS: We conducted a prospective randomized controlled trial of vaginal preparation with 0.5% chlorhexidine gluconate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…This review identified very little research published related to chlorhexidine solutions. In other surgical specialties such as cardiac, orthopedic, and gynecological surgery, chlorhexidine has been used with minimal evidence of tissue toxicity [43,44]. However, in the case of vaginal preparation PVP-I was shown to be more effective [44].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This review identified very little research published related to chlorhexidine solutions. In other surgical specialties such as cardiac, orthopedic, and gynecological surgery, chlorhexidine has been used with minimal evidence of tissue toxicity [43,44]. However, in the case of vaginal preparation PVP-I was shown to be more effective [44].…”
Section: Discussionmentioning
confidence: 99%
“…In other surgical specialties such as cardiac, orthopedic, and gynecological surgery, chlorhexidine has been used with minimal evidence of tissue toxicity [43,44]. However, in the case of vaginal preparation PVP-I was shown to be more effective [44]. Also, it has been demonstrated that surgeons should be hesitant in mixing chlorhexidine with other antiseptics as precipitate can form and lead to complications [45].…”
Section: Discussionmentioning
confidence: 99%
“…The researchers had intentionally selected a low CHG concentration for the study (ie, 0.5%) to minimize vaginal burning and irritation; they noted that mild irritation can occur with PI antiseptics. 17 Another study compared the rates of symptomatic urinary tract infection (UTI) after application of either 10% PI or 2% CHG for vaginal antisepsis in 119 patients undergoing urogynecological procedures. 38 The primary outcome reflected the patients' symptoms during the two-week follow-up visit.…”
Section: Randomized Controlled Trialsmentioning
confidence: 99%
“… leaves a topical yellow residual stain; 10 may cause chemical burns, 11 skin irritation, 12 and allergic reactions, 13 including anaphylaxis; 14 has minimal persistence; 12,15 is inactivated in the presence of blood and other body fluids, serum proteins, other organic matter, 12,15 and the acidic environment 16 of the vagina; 17 and may be absorbed through the vagina and into the circulatory system 18,19 …”
Section: Review Of the Literaturementioning
confidence: 99%
“…One frequently sited rationale is that CHG is not deactivated in the presence of blood. The literature is mixed with regard to which method better prevents of SSI [47 ▪ ,48 ▪ ,49 ▪ ,50]. ACOG supports use of either solution [26].…”
Section: Intraoperative Risk Factorsmentioning
confidence: 99%